The Political Response of Spanish Youth to the Socio-Economic Crisis: Some Implications for Citizenship Education - Gonzalo Jover; Maria Belando Montoro; Yolanda Guio (Journal of Social Science Education, 2014)
This article discusses the effects of the current socio-economic crisis on Spanish youth and their political response to it. It does so in three consecutive stages. In the first, it analyses the repercussion of the crisis on young people using information from certain social indicators (employment, mobility and education). It then outlines the subjective perception of the crisis, i.e., how they are experiencing it and what their hopes are regarding the economy and politics. The third part focuses on how young citizens have responded to the situation politically. The article finishes by considering what implications may be drawn from that response in terms of citizenship education.